Проблемы уголовно-правовой ответственности за незаконное потребление электрической энергии - Семенович, Кристина (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the problem of the legal responsibility for illegal consumption of the electric energy. The author present the problem of illegal power consumption, characteristics of the criminal acts in the area of energy consumption, Russian legislative measures and the examples of approaches of the foreign lawmakers.